Does vocational education pay off in China? Instrumental-variable quantile-regression evidence - Li Dai; Pedro S. Martins (Global Labor Organization (GLO), 2020)
As China's firms upgrade their position in the quality ladder, vocational education may become more important. In this paper, we study returns to secondary vocational education in China paying attention to individual heterogeneity. We use instrumental variables based on geographical and longitudinal changes in enrolment to address the selection between the two types of education. We find that vocational education provides a wage premium vis-à-vis academic education of over 30% but which applies only for individuals at the middle of the conditional wage distribution.
Keywords: I26; I25; J24; J31; C36; 330; Human capital; vocational education; quantile treatment effects